(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe and identify some factors related to insomnia in cirrhotic patients at the Gastroenterology Department - Viet Tiep Friendship Hospital in 2025. Method: Cross-sectional descriptive study, convenient sampling on 116 cirrhotic patients. Results: The proportion of respondents with insomnia was 66.38%; of which moderate insomnia accounted for the highest proportion at 44.1%; mild insomnia accounted for 31.2%; and severe insomnia accounted for 24.7%. Analysis of some related factors showed: There was a statistically significant correlation between the severity of insomnia and disease stage, pain level, and anxiety level (p < 0.05). Conclusion: The majority of cirrhotic patients (66.38%) suffered from insomnia, with severe insomnia accounting for 24.7%. There was a correlation between insomnia and disease stage, pain level, and anxiety level. Therefore, to improve sleep for patients with cirrhosis, it is necessary to focus on reducing pain and anxiety, especially in patients with decompensated cirrhosis.